2019
DOI: 10.17344/acsi.2018.4783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA/BSA Binding and Chemical Nuclease Activity of L-Tyrosine-Based Mn(III) and Fe(III) Metallo-Intercalators

Abstract: A novel class of Mn(III) and Fe(III) complexes of L-tyrosine-based ligand has been synthesized and characterized through various analytical and spectroscopic techniques. These complexes were found to exhibit efficient binding properties with the biomolecules viz. calf thymus DNA and BSA. The ability of complexes to bind with such biomolecules has been explored through absorption, emission and viscosity measurements. Based on spectroscopic techniques we can conclude that the complexes could bind to DNA via inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…[ 34 ] The broad band observed in the region of 3450–3540 cm −1 corresponds to the OH stretching vibrations of the lattice water molecules. [ 35 ] All the three complexes exhibited a band at 955–960 cm −1 which can be ascribed to ν (VO) stretching frequency. [ 36 ] Because the VO stretching has not been shifted to lower wavenumber region, it is confirmed that there is no interaction between vanadyl oxygen of one molecule and vanadium of another molecule (VO ...… VO).…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] The broad band observed in the region of 3450–3540 cm −1 corresponds to the OH stretching vibrations of the lattice water molecules. [ 35 ] All the three complexes exhibited a band at 955–960 cm −1 which can be ascribed to ν (VO) stretching frequency. [ 36 ] Because the VO stretching has not been shifted to lower wavenumber region, it is confirmed that there is no interaction between vanadyl oxygen of one molecule and vanadium of another molecule (VO ...… VO).…”
Section: Resultsmentioning
confidence: 99%